Criança é presente : pistas para uma hermenêutica bíblica na perspectiva de crianças - Lamb, Regene (2008)
A child is a present : Clues for a biblical hermeneutic on the perspective of children. The first part of this dissertation brings some theoretical references from the social sciences with special emphasis on child anthropology, on gender matters and on the matters of children agency. It shows how far universal concepts of childhood are from the concrete life of children, since they always come with the marks of time on which they are insert. The second part shows the biblical text of John 6,1-15, where a child is the one who brings bread and fish to be shared. Highlighted are some aspects related to place, time interconnections among adults and children and parallels are drawn with the sinoptical gospels. The text is brought in his literary context and some specific theological issues of John s Gospel are showed. The third and last chapter approaches the symbolic hermeneutics, asking about the reality of children on Jesus time and shows the commitment of the early Christian Communities with the children. Finally, it indicates some assumptions that will orient the reading of the Bible as well as the pastoral work with children: it isn't possible to speak about one generation without considering another; children are completed beings and they answer to the stimulus they receive from those who are related to them since the beginning of their lives; it is possible to develop a theology with children if we, as adults, are willing to learn with them and, above all, if we seek for places and time for acquaintanceship. This will allow the entertainment, friendship , the valorization of the symbolic and of the metaphors ; children and adults are all the time interconnected. We will only discover the agency of children in the origins of Christian movement if we ask for it explicitly and if we really commit ourselves with projects that valorize the children for what they are in the present.